Approval status and evidence for WHO essential medicines for children in the United States, United Kingdom, and Japan: a cross-sectional study. Issue 1 (December 2017) - Shimazawa, Rumiko; Ikeda, Masayuki
Abstract Background The WHO Model List of Essential Medicines for Children (EMLc) covers medicines for globally high-burden diseases. Regulatory approval in high-income countries ensures evidence and dosage form but usually focuses on diseases common in those countries and not in low- and middle-income countries. Methods This cross-sectional study assessed supporting evidence for the 346 medicines in the 5th WHO EMLc and their approval data from the United States, United Kingdom, and Japan. Results Of the 346 EMLc medicines, 307 were approved in one or more of the three countries, 278 of which had supporting evidence of efficacy. The percentage of medicines approved in one or more of the three countries was lowest for antiparasitics (60%) whereas 100% for medicines for cancers and musculoskeletal and respiratory conditions were approved. Five of the 30 EMLc antineoplastics had no supporting paediatric evidence. Of the 39 EMLc medicines unapproved in all three countries, 26 were indicated for neglected infectious diseases (NIDs). Ten of the 26 had supporting paediatric evidence. Seventeen of the 39 unapproved medicines had no paediatric dosage form available, and all 17 were indicated for NIDs. Conclusions Most EMLc medicines for diseases common in the three countries had supporting evidence, which was closely associated with approval, whereas a substantial number of medicines for NIDs were unapproved in the three countries, regardless of whether they had supporting evidence. Because of the limited contribution to the EMLc from high income countries, appropriate incentive mechanisms for pharmaceutical companies are required to make paediatric development for NIDs feasible and effective.